Children who have received no routine polio vaccines in Nigeria: Who are they and where do they live? - Uthman, Olalekan A.; Adedokun, Sulaimon T.; Olukade, Tawa; Watson, Samuel; Adetokunboh, Olatunji; Adeniran, Adeyinka; Oyetoyan, Solomon A.; Gidado, Saheed; Lawoko, Stephen; Wiysonge, Charles S. (Human Vaccines & Immunotherapeutics, 2017)
2016; putting an end to 2 y without reported cases. We examined the extent of geographical disparities in childhren not vaccinated against polio and examined individual- and community-level predictors of nonvaccination in Nigeria. We applied multilevel logistic regression models to the recent Nigeria Demographic and Health Survey. The percentage of children not routinely vaccinated against polio in Nigeria varied greatly and clustered geographically, mainly in north-eastern states, with a great risk of spread of transmission within these states and potential exportation to neighboring states and countries. Only about one-third had received all recommended 4 routine oral polio vaccine doses. Non-vaccinated children tended to have a mother who had no formal education and who was currently not working, live in poorer households and were from neighborhoods with higher maternal illiteracy rates.
Keywords: Children; Polio vaccines